Preparation method of high-thermal-conductivity spherical structure multiphase component ceramic powder
By preparing high-thermal conduction spherical structure composite component ceramic powder, the problem of insufficient thermal conductivity of ceramic materials is solved by using mesoporous structure and nitriding reaction, the preparation of high-thermal conductivity and high-insulating ceramic materials is achieved, and the ceramic materials are improved. Overall performance.
Patent Information
- Application Number
- CN202411083925.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-08
AI Technical Summary
Traditional ceramic materials have insufficient thermal conductivity and are difficult to meet the needs of high thermal conductivity, high insulation and high voltage resistance.
By preparing high-thermal conductivity spherical structure composite component ceramic powder, including preparing soluble metal salt solution, spray-drying to form mesoporous structure spherical powder, the first heating is obtained to obtain oxide spherical ceramic powder, and the mixture slurry and metal salt are prepared. In combination, the second heating is nitrided in a nitrogen atmosphere to form a highly thermally conductive spherical structure composite component ceramic powder.
The high thermal conductivity and high insulation of ceramic materials are achieved, the thermal conductivity is enhanced, and the densification problem is avoided, ensuring the stability and performance of the structure are improved.
Abstract
Description
Technical Field
[0001] The invention relates to ceramic powder, and in particular to the field of a method for preparing ceramic powder with a high thermal conductivity spherical structure and multi-phase components. Background Art
[0002] With the rapid development of the information age, the development of industrial technology and the improvement of people's living standards, higher requirements have been put forward for the higher performance and miniaturization of industrial electronic power products and consumer products, and the requirements for thermal conductive fillers are getting higher and higher. Conventional inorganic thermal conductive medium materials can no longer meet the needs of high thermal conductivity, high insulation and high voltage resistance, while ceramic materials meet the requirements of high insulation materials. Now the thermal conductivity of traditional ceramic materials needs to be further improved.
[0003] Therefore, how to improve the thermal conductivity of ceramic materials while meeting high insulation requirements has become an urgent problem to be solved in this field. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder, so that the prepared high thermal conductivity spherical structure multi-phase component ceramic powder has high thermal conductivity and high insulation.
[0005] The present invention provides a method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder, which is characterized by comprising the following steps:
[0006] preparing a first soluble metal salt solution, the first soluble metal salt solution comprising a first metal salt;
[0007] preparing a crystalline foam slurry by using the first soluble metal salt solution;
[0008] The crystalline foam slurry is spray-dried to obtain a mesoporous spherical powder A;
[0009] The mesoporous spherical powder A is subjected to a first heating to obtain an oxide spherical ceramic powder B; the maximum temperature of the first heating is 600-1000° C.;
[0010] The oxide spherical ceramic powder B is prepared into a first mixed slurry, wherein the first mixed slurry includes a second auxiliary agent and a third auxiliary agent;
[0011] Mixing a mixed slurry with a second soluble metal salt to obtain a second mixed slurry;
[0012] Granulating the second mixed slurry to obtain spherical ceramic powder C;
[0013] The spherical ceramic powder C is heated for a second time in a reaction gas atmosphere to obtain a high thermal conductivity spherical structure multi-phase component ceramic powder; the reaction gas includes nitrogen.
[0014] Compared with the prior art, the present invention has the beneficial effect that, by preparing a crystalline foam slurry from a first soluble metal salt solution, the crystalline foam slurry is spray-dried, so that the obtained mesoporous spherical powder A has a spherical structure and a mesh structure inside; this structure is conducive to the discharge of volatiles in the mesoporous spherical powder A and is not prone to structural deformation or damage;
[0015] The mesoporous spherical powder A is heated at a temperature of 600-1000° C. to obtain an oxide spherical ceramic powder B which has high strength and certain activity, and the oxide spherical ceramic powder B has an internal mesh structure and a uniform sphere on the outside, and the volatile substances in the mesoporous spherical powder A have been completely discharged. After the volatile substances are discharged at a temperature of 600-1000° C., the surface of the oxide spherical ceramic powder B has certain pores, and the problem of densification of the pores under high temperature conditions is avoided, thereby avoiding the problem that the subsequent second soluble metal salt cannot enter the interior of the oxide spherical ceramic powder B;
[0016] The first mixed slurry includes a second auxiliary agent and a third auxiliary agent, and a mixed slurry is mixed with a second soluble metal salt to obtain a second mixed slurry; this is beneficial for the second auxiliary agent to enter the oxide spherical ceramic powder B after combining with the metal salt; the third auxiliary agent is beneficial for the third auxiliary agent to enter the oxide spherical ceramic powder B and then perform surface modification on the network inside the oxide spherical ceramic powder B, and the modified network structure is beneficial for combining with the metal salt combined with the second auxiliary agent, thereby achieving uniform filling of the metal salt inside the oxide spherical ceramic powder B with high bonding strength.
[0017] The spherical ceramic powder C is heated for a second time in a reaction gas atmosphere to obtain a high thermal conductivity spherical structure multiphase component ceramic powder; the reaction gas includes nitrogen, so that the metal salt bound inside the oxide spherical ceramic powder B is subjected to a nitridation reaction to form a nitride ceramic, thereby achieving the internal and external densification of the oxide spherical ceramic powder B, and during the entire second heating process, the oxide spherical ceramic powder B has a large number of pore channels on its surface, which is conducive to the discharge of volatiles, and is conducive to the nitridation of the reaction gas and metal ions during and after the discharge of the volatiles, thereby obtaining a high thermal conductivity spherical structure multiphase component ceramic powder with dense interior and surface;
[0018] The spherical ceramic powder C is obtained by granulating the second mixed slurry, which is conducive to the final high thermal conductivity spherical structure multiphase component ceramic powder being spherical, and further enhancing the thermal conductivity;
[0019] Ultimately, the high thermal conductivity spherical structure multiphase component ceramic powder has high thermal conductivity and high insulation.
[0020] Furthermore, the preparation process of the first soluble metal salt solution is to mix and stir the first soluble metal salt, water, a surfactant, and a first auxiliary agent in a mass ratio of (15-20): (75-85): (0.45-1.25): (0.0075-0.0325) to obtain the first soluble metal salt solution.
[0021] Further, the first metal salt includes one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, magnesium nitrate, magnesium chloride, and silicon chloride;
[0022] The surfactant includes sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium bromide and / or octadecyltrimethylammonium bromide; the first auxiliary agent includes calcium oxide and magnesium oxide.
[0023] Further, the process for preparing the crystalline foam slurry comprises the following steps:
[0024] The first soluble metal salt solution is stirred at an ambient temperature of 60-100° C., with a stirring speed of ≥1400 r / min.
[0025] The beneficial effect of adopting the previous step is that the soluble metal salt is hydrolyzed and the soluble metal salt crystals are allowed to grow into dense crystalline foam slurry.
[0026] Furthermore, the first heating process of the mesoporous spherical powder A is as follows: heating to 90-100°C at a heating rate of 9-10°C / min; heating from 90-100°C to 280-320°C at a heating rate of 6-7°C / min; heating from 280-320°C to 480-520°C at a heating rate of 3-4°C / min; heating from 480-520°C to 600-1000°C at a heating rate of 5-6°C, and the heating time at 600-1000°C is 5.5-6.5h.
[0027] The beneficial effect of the above step is that by heating to 90-100°C at a heating rate of 9-10°C / min, small molecular volatiles are rapidly volatilized, small pore channels are formed on the surface of the mesoporous spherical powder A, and the structure of the mesoporous spherical powder A is not damaged; by heating from 90-100°C to 280-320°C at a heating rate of 6-7°C / min, large molecular volatiles are slowly decomposed, and the remaining small molecular volatiles are completely volatilized; by heating from 280-320°C to 480-520°C, with a heating rate of 3-4°C / min, the decomposed macromolecular volatiles are slowly volatilized on the basis of the small-pore channels formed by the previous volatilization of small molecules, thereby avoiding damage to the structure of the mesoporous spherical powder A; by heating from 480-520°C to 600-1000°C, with a heating rate of 5-6°C, and a heating time of 5.5-6.5h at 600-1000°C, the strength of the mesoporous spherical powder A is increased, while retaining a certain activity and the surface pores are not densified.
[0028] Furthermore, the preparation process of the first mixed slurry is to mix the oxide spherical ceramic powder B with water, then add the second auxiliary agent and the third auxiliary agent, and stir at room temperature under negative pressure, with a stirring speed of ≤400r / min and a negative pressure range of -0.08 to -0.12MPa.
[0029] Furthermore, the mass ratio of the oxide spherical ceramic powder B, water, the second auxiliary agent, and the third auxiliary agent is (12-18): (76-80): (0.55-0.75): (0.0155-0.0175);
[0030] The second auxiliary agent includes one or two of ethylenediamine, cyclohexane, propylene oxide, and N,N-dimethylamide;
[0031] The third auxiliary agent includes a silane coupling agent.
[0032] Furthermore, the second mixed slurry preparation process is to add the second soluble metal salt into the first mixed slurry, and stir it under negative pressure at room temperature, with a stirring speed of ≤400r / min and a negative pressure range of -0.08 to -0.12MPa;
[0033] The mass ratio of the second soluble metal salt to the oxide spherical ceramic powder B is (16-20):(80-84);
[0034] The second soluble metal salt includes aluminum trichloride and / or aluminum sulfate.
[0035] The beneficial effect of adopting the previous step is that it is conducive to modifying the internal network surface of the oxide spherical ceramic powder B by a silane coupling agent, and at the same time, the second soluble metal salt is conducive to entering the interior of the oxide spherical ceramic powder B after combining with the second auxiliary agent, and is combined with the internal network of the modified oxide spherical ceramic powder B, and the bonding strength is high; and through the ratio of the oxide spherical ceramic powder B, water and the second soluble metal salt, while realizing the addition of each material to the interior of the oxide spherical ceramic powder B, it is conducive to increasing the solid content of the second mixed slurry entering the interior of the oxide spherical ceramic powder B, and improving the density of the interior of the oxide spherical ceramic powder B without affecting the subsequent full and uniform nitridation reaction of the metal salt and the reaction gas;
[0036] The second soluble metal salt includes aluminum chloride and / or aluminum sulfate, which is beneficial to further improve the thermal conductivity of the high thermal conductivity spherical structure multi-phase component ceramic powder.
[0037] Furthermore, the particle size of the oxide spherical ceramic powder B is 30-40 μm; and the particle size of the high thermal conductivity spherical structure multiphase component ceramic powder is 40-60 μm.
[0038] Furthermore, the process of heating the spherical ceramic powder C for the second time is as follows: placing the spherical ceramic powder C in a closed space and then evacuating the space, and then introducing a reaction gas after stopping the evacuation, and maintaining the gas pressure in the closed space at 3-8 MPa; and then heating and calcining at 1300-1900° C. for 9.5-10.5 hours to obtain a high thermal conductivity spherical structure multiphase component ceramic powder;
[0039] Preferably, the reaction gas also includes hydrogen; preferably, the high thermal conductivity spherical structure multiphase component ceramic powder has an electrical conductivity of ≥340W, a resistance of ≥1015 ohms, and a bulk density of 0.28-0.32g / cm 3 .
[0040] The beneficial effect of adopting the previous step is that it is conducive to nitriding and ceramicizing the metal ions bonded to the grid structure of the oxide spherical ceramic powder B contained in the spherical ceramic powder C, and densifying the interior, while achieving ceramicization and densification of the surface of the spherical ceramic powder C;
[0041] The reaction gas also includes hydrogen, which is beneficial to the discharge of oxygen elements and further beneficial to the nitridation of metal elements; ultimately, the prepared high thermal conductivity spherical structure multiphase component ceramic powder has high thermal conductivity and high insulation. DETAILED DESCRIPTION
[0042] In order to better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments.
[0043] Embodiment 1:
[0044] This embodiment provides a method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder, characterized in that it includes the following steps:
[0045] A first soluble metal salt solution is prepared, wherein the first soluble metal salt solution includes a first metal salt; the preparation process of the first soluble metal salt solution is to mix and stir the first soluble metal salt, water, a surfactant, and a first auxiliary agent in a mass ratio of 18:80:0.83:0.02 to obtain the first soluble metal salt solution;
[0046] The first metal salt includes silicon chloride;
[0047] The surfactant includes sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium bromide; the first auxiliary agent includes calcium oxide and magnesium oxide.
[0048] The crystalline foam slurry is prepared by using the first soluble metal salt solution. The process of preparing the crystalline foam slurry includes the following steps: stirring the first soluble metal salt solution at an ambient temperature of 80° C. and a stirring speed of 1700 r / min.
[0049] The crystalline foam slurry is spray-dried to obtain a mesoporous spherical powder A;
[0050] The mesoporous spherical powder A is heated for the first time to obtain the oxide spherical ceramic powder B; the maximum temperature of the first heating is 800°C; the particle size of the oxide spherical ceramic powder B is 35μm; the first heating process of the mesoporous spherical powder A is as follows: heating to 95°C at a heating rate of 9.5°C / min; heating from 95°C to 300°C at a heating rate of 6.5°C / min; heating from 300°C to 500°C at a heating rate of 3.5°C / min; heating from 500°C to 800°C at a heating rate of 5.5°C, and the heating time at 8000°C is 6h.
[0051] The oxide spherical ceramic powder B is prepared into a first mixed slurry, wherein the first mixed slurry includes a second auxiliary agent and a third auxiliary agent; the first mixed slurry is prepared by mixing the oxide spherical ceramic powder B with water, then adding the second auxiliary agent and the third auxiliary agent, and stirring at room temperature under negative pressure, with a stirring speed of 300 r / min and a negative pressure of -0.1 MPa;
[0052] The mass ratio of the oxide spherical ceramic powder B, water, the second auxiliary agent and the third auxiliary agent is 20:78:0.65:0.0165; the second auxiliary agent includes ethylenediamine and cyclohexane; and the third auxiliary agent includes a silane coupling agent.
[0053] A mixed slurry is mixed with a second soluble metal salt to obtain a second mixed slurry; the preparation process of the second mixed slurry is to add the second soluble metal salt into the first mixed slurry, and stir it under negative pressure at room temperature, with a stirring speed of 300r / min and a negative pressure of -0.10MPa; the mass ratio of the second soluble metal salt to the oxide spherical ceramic powder B is 18:82; the second soluble metal salt includes aluminum trichloride.
[0054] Granulating the second mixed slurry to obtain spherical ceramic powder C;
[0055] The spherical ceramic powder C is heated for a second time in a reaction gas atmosphere to obtain a high thermal conductivity spherical structure multi-phase component ceramic powder; the reaction gas includes nitrogen; the high thermal conductivity spherical structure multi-phase component ceramic powder has a particle size of 50 μm;
[0056] The process of heating the spherical ceramic powder C for the second time is as follows: placing the spherical ceramic powder C in a closed space and then evacuating the space, and then introducing a reaction gas to maintain the gas pressure in the closed space at 5.5 MPa after stopping the evacuation; and then heating and calcining the spherical ceramic powder at 1600° C. for 10 hours to obtain a ceramic powder with a spherical structure and a multi-phase component having high thermal conductivity;
[0057] The high thermal conductivity spherical structure multiphase component ceramic powder has an electrical conductivity of ≥360W, a resistance of ≥1050 ohms, and a bulk density of 0.3g / cm 3 .
[0058] Embodiment 2:
[0059] The same contents as those in Example 1 are not described in detail here. The differences between this embodiment and Example 1 are as follows: the first soluble metal salt solution is prepared by mixing and stirring a first soluble metal salt, water, a surfactant, and a first auxiliary agent in a mass ratio of 16:76:0.55:0.0085 to obtain the first soluble metal salt solution;
[0060] The first metal salt includes aluminum chloride, magnesium nitrate, and silicon chloride;
[0061] The surfactant includes sodium dodecylbenzene sulfonate and octadecyltrimethylammonium bromide.
[0062] The process for preparing the crystalline foam slurry comprises the following steps: stirring the first soluble metal salt solution at an ambient temperature of 60-100° C. at a stirring speed of 1600 r / min.
[0063] The maximum temperature of the first heating is 700°C; the particle size of the oxide spherical ceramic powder B is 32μm; the first heating process of the mesoporous spherical powder A is as follows: heating to 92°C at a heating rate of 9.2°C / min; heating from 92°C to 290°C at a heating rate of 6.2°C / min; heating from 290°C to 490°C at a heating rate of 3.2°C / min; heating from 490°C to 700°C at a heating rate of 5.2°C, and the heating time at 700°C is 6.2h.
[0064] The preparation process of the first mixed slurry is to mix the oxide spherical ceramic powder B with water, then add the second auxiliary agent and the third auxiliary agent, and stir at room temperature under negative pressure, with a stirring speed of ≤260r / min and a negative pressure of -0.085MPa;
[0065] The mass ratio of the oxide spherical ceramic powder B, water, the second auxiliary agent, and the third auxiliary agent is 13:78:0.58:0.0158; the second auxiliary agent includes propylene oxide and N,N-dimethylamide. The second mixed slurry preparation process is to add the second soluble metal salt to the first mixed slurry, stir it under negative pressure at room temperature, the stirring speed is 280r / min, and the negative pressure is -0.085MPa; the mass ratio of the second soluble metal salt to the oxide spherical ceramic powder B is 17:83; the second soluble metal salt includes aluminum sulfate.
[0066] The particle size of the high thermal conductivity spherical structure multi-phase component ceramic powder is 43 μm;
[0067] The process of heating the spherical ceramic powder C for the second time is as follows: placing the spherical ceramic powder C in a closed space and then evacuating the space, and then introducing a reaction gas after stopping the evacuation, wherein the reaction gas includes nitrogen and hydrogen; maintaining the gas pressure in the closed space at 4 MPa; and then heating and calcining at 1500° C. for 10.2 hours to obtain a high thermal conductivity spherical structure multiphase component ceramic powder;
[0068] The high thermal conductivity spherical structure multi-phase component ceramic powder has an electrical conductivity of ≥350W, a resistance of ≥1030 ohms, and a bulk density of 0.29 g / cm 3 .
[0069] Embodiment 3:
[0070] The same contents as those in Example 1 are not repeated here. The differences between this embodiment and Example 1 are as follows: the preparation process of the first soluble metal salt solution is to mix and stir the first soluble metal salt, water, surfactant, and first auxiliary agent in a mass ratio of 19:83:1.23:0.030 to obtain the first soluble metal salt solution;
[0071] The first metal salt includes aluminum nitrate, magnesium nitrate, and silicon chloride;
[0072] The surfactant includes sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide and octadecyltrimethylammonium bromide.
[0073] The process for preparing the crystalline foam slurry comprises the following steps: stirring the first soluble metal salt solution at an ambient temperature of 95° C. and a stirring speed of 1800 r / min.
[0074] The maximum temperature of the first heating is 950°C; the particle size of the oxide spherical ceramic powder B is 38μm; the first heating process of the mesoporous spherical powder A is as follows: heating to 98°C at a heating rate of 9.8°C / min; heating from 98°C to 310°C at a heating rate of 6.8°C / min; heating from 310°C to 510°C at a heating rate of 3.8°C / min; heating from 510°C to 950°C at a heating rate of 5-6°C, and the heating time at 600-1000°C is 5.5-6.5h.
[0075] The preparation process of the first mixed slurry is to mix the oxide spherical ceramic powder B with water, then add the second auxiliary agent and the third auxiliary agent, and stir at room temperature under negative pressure, with a stirring speed of ≤380r / min and a negative pressure of -0.11MPa;
[0076] The mass ratio of the oxide spherical ceramic powder B, water, the second auxiliary agent, and the third auxiliary agent is 17:79:0.73:0.0173; the second auxiliary agent includes cyclohexane and N,N dimethylamide. The second mixed slurry preparation process is to add the second soluble metal salt to the first mixed slurry, stir it under negative pressure at room temperature, the stirring speed is 380r / min, and the negative pressure is -0.11MPa; the mass ratio of the second soluble metal salt to the oxide spherical ceramic powder B is 19:81. The second soluble metal salt includes aluminum chloride and aluminum sulfate.
[0077] The particle size of the high thermal conductivity spherical structure multi-phase component ceramic powder is 58 μm;
[0078] The process of heating the spherical ceramic powder C for the second time is as follows: placing the spherical ceramic powder C in a closed space and then evacuating the space, and then introducing a reaction gas after stopping the evacuation, wherein the reaction gas includes nitrogen and hydrogen; maintaining the gas pressure in the closed space at 7 MPa; and then heating and calcining at 1850° C. for 9.3 hours to obtain a high thermal conductivity spherical structure multiphase component ceramic powder;
[0079] The high thermal conductivity spherical structure multi-phase component ceramic powder has an electrical conductivity of ≥380W, a resistance of ≥1060 ohms, and a bulk density of 0.31 g / cm 3 .
[0080] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features have similar functions to those disclosed in the present application (but not limited to).
Claims
1. A method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder, characterized in that: The following steps are involved: preparing a first soluble metal salt solution, the first soluble metal salt solution comprising a first metal salt; preparing a crystalline foam slurry by using the first soluble metal salt solution; The crystalline foam slurry is spray-dried to obtain a mesoporous spherical powder A; The mesoporous spherical powder A is subjected to a first heating to obtain an oxide spherical ceramic powder B; the maximum temperature of the first heating is 600-1000° C.; The oxide spherical ceramic powder B is prepared into a first mixed slurry, wherein the first mixed slurry includes a second auxiliary agent and a third auxiliary agent; Mixing a mixed slurry with a second soluble metal salt to obtain a second mixed slurry; Granulating the second mixed slurry to obtain spherical ceramic powder C; The spherical ceramic powder C is heated for a second time in a reaction gas atmosphere to obtain a high thermal conductivity spherical structure multi-phase component ceramic powder; the reaction gas includes nitrogen.
2. The method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder according to claim 1, characterized in that: The preparation process of the first soluble metal salt solution is to mix and stir the first soluble metal salt, water, a surfactant, and a first auxiliary agent in a mass ratio of (15-20): (75-85): (0.45-1.25): (0.0075-0.0325) to obtain the first soluble metal salt solution.
3. The method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder according to claim 2, characterized in that: The first metal salt includes one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, magnesium nitrate, magnesium chloride, and silicon chloride; The surfactant includes sodium dodecylbenzene sulfonate and hexadecyltrimethylammonium bromide and / or octadecyltrimethylammonium bromide; The first auxiliary agent includes calcium oxide and magnesium oxide.
4. The method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder according to claim 1, characterized in that: The process of preparing the crystalline foam slurry comprises the following steps: The first soluble metal salt solution is stirred at an ambient temperature of 60-100° C., with a stirring speed of ≥1400 r / min.
5. The method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder according to claim 1, characterized in that: The first heating process of the mesoporous spherical powder A is as follows: heating to 90-100°C at a heating rate of 9-10°C / min; heating from 90-100°C to 280-320°C at a heating rate of 6-7°C / min; heating from 280-320°C to 480-520°C at a heating rate of 3-4°C / min; heating from 480-520°C to 600-1000°C at a heating rate of 5-6°C, and the heating time at 600-1000°C is 5.5-6.5h.
6. The method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder according to claim 1, characterized in that: The preparation process of the first mixed slurry is to mix the oxide spherical ceramic powder B with water, then add the second auxiliary agent (complex) and the third auxiliary agent (coupling agent), and stir at room temperature under negative pressure. The stirring speed is ≤400r / min, and the negative pressure range is -0.08 to -0.12MPa.
7. The method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder according to claim 1, characterized in that: The mass ratio of the oxide spherical ceramic powder B, water, the second auxiliary agent (complex), and the third auxiliary agent (coupling agent) is (12-18): (76-80): (0.55-0.75): (0.0155-0.0175); The second auxiliary agent includes one or two of ethylenediamine, cyclohexane, propylene oxide, and N,N-dimethylamide; The third auxiliary agent includes a silane coupling agent.
8. The method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder according to claim 1, characterized in that: The second mixed slurry preparation process is to add the second soluble metal salt into the first mixed slurry, and stir it under negative pressure at room temperature, with a stirring speed of ≤400r / min and a negative pressure range of -0.08 to -0.12MPa; The mass ratio of the second soluble metal salt to the oxide spherical ceramic powder B is (16-20):(80-84); The second soluble metal salt includes aluminum trichloride and / or aluminum sulfate.
9. The method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder according to claim 1, characterized in that: The particle size of the oxide spherical ceramic powder B is 30-40 μm; The particle size of the high thermal conductivity spherical structure multi-phase component ceramic powder is 40-60 μm.
10. The method for preparing a high thermal conductivity spherical structure multi-phase component ceramic powder according to claim 1, characterized in that: The process of heating the spherical ceramic powder C for the second time is as follows: placing the spherical ceramic powder C in a closed space and then evacuating the space, introducing reaction gas after stopping the evacuation, and maintaining the gas pressure in the closed space at 3-8 MPa; then heating and calcining at 1300-1900°C for 9.5-10.5 hours to obtain a high thermal conductivity spherical structure multiphase component ceramic powder.
Citation Information
Patent Citations
Method for synthesizing AlN ceramic powder through organic network
CN105884372A
Preparation method of high-purity sphere-like nanometer AlN (aluminum nitride) particle
CN108862216A
Preparation method of aluminum nitride powder
CN116396082A
Method for preparing spherical aluminum nitride powder through precursor spray granulation
CN117720352A
Highly filled high thermal conductive material, method for manufacturing same, composition, coating liquid and molded article
US20150259589A1
